Gençlerin Öğrenim Yaşamı Boyunca Okul İklimi Deneyimleri - Alkan, Baran; Ertuğrul , Elif Gizem; Gözaydın, Kerem; Tosun, Yağmur Sena; Akyol, Aslı; Sığındı, İrem; Eken, Damla; Sözeri, Elif; Özayaşlıol, Salih; Atak, Şükrü; Özden, Mustafa Enes; Çoban, Tülin; et al. (Turkey Health Literacy Journal, 2023)
AbstractObjective: The aim of the study is to evaluate the university school climate of the students and to investigate the mistreatment from teachers that students are exposed to throughout their education life.Method: The research datas are collected with the Questionnaire for the demographic information of the students, the University Climate Scale and the Educational Violance Experience Questionnaire.Results: The sample of this study included 425 medical faculty students; the average age of the participants is 22,33 (SD:2,25). The 51.8% of participants stated that they had been exposed to trainer mistreatment. The participants were exposed to verbal mistreatment in primary school with the highest 22.4%, were exposed to emotional mistreatment in high school with the highest 19.5%, were exposed to emotional mistreatment with the highest 26.6 at the university. The 34.1% of participants evaluated the university climate as positive (open), while 28.5% evaluated the university climate as negative (closed). While 48,8% of the participants who evaluated the university climate as negative stated that they were exposed to mistreatment. It is fact that there is a significant relationship between the participants who stated that they were exposed to mistreatment and the more negative (closed) evaluation of the university climate (p
Keywords: Mistreatment, trainer violance, violance, school climate.